Economia de dados, capitalismo de vigilância e erosão dos fatos na política democrática - Oliveira, José Adeildo Bezerra de (2023)
This research aims to understand the deleterious effects of the personal data economy on factual matter, democratic politics, and fundamental rights. The starting point of the reflection was the misinformation caused by fake news. Thus, this research seeks to understand how misinformation is fissuring the truth about facts and democratic politics and expose the relationship of this with the business model based on personal data economy, algorithmic regulation, and obscure mediation of public speech in the virtual environment by big tech. The central theoretical references used for this part of the reflection are Hannah Arendt and Shoshana Zuboff. Based on Arendt, it was noted that there is a historical conflict between truth and politics, between truth and power. However, the problem was reformulated in order to understand this historical conflict as a clash between the neoliberal economic logic of surveillance capitalism and the reality of facts and fundamental rights. Thus, it is concluded that the problem behind fake news and misinformation must be understood from another perspective than the mere reach given to misinformation by digital technical infrastructure but from a neoliberal and market ideological perspective, based on commercial exploitation of users’ personal data and the consequent use of human sensitivities to capture their attention and extract their data. Therefore, the problem to be faced by current democracies is structural, economic, and political logic, not means. The diagnosis led to reflections on the role of the regulatory state in combating violations of fundamental rights. Therefore, regulatory models under discussion in the national and international political agenda are exposed, highlighting the Brazilian regulatory framework, with its limits and possibilities. It was identified that the Brazilian debate is centered on forms of platform accountability for third-party content and combating hate speech and fake news. The Hypothetical-Deductive method was used. The research objectives adopted the exploratory method. Regarding the procedures, the methodology adopted was bibliographic research. As for the methodological approach, the qualitative approach was adopted.